Microstructure and corrosion behaviour of A356 aluminium alloy modified with Nd. Issue 6 (8th July 2014) - Arrabal, R.; Mingo, B.; Pardo, A.; Mohedano, M.; Matykina, E.; Merino, M. C.; Rivas, A.
<x xml:space="preserve">Abstract</x> The microstructure of a gravity‐cast A356 aluminium alloy modified with 0.4 wt% Nd and its corrosion behaviour in 3.5 wt% NaCl solution is investigated. The addition of Nd refines the eutectic silicon and results in the formation of Nd‐containing intermetallics, which show smaller potential differences relative to the α‐Al matrix than the Fe‐rich intermetallics in the unmodified alloy. In 3.5 wt% NaCl solution, A356 and A356Nd alloys reveal localized corrosion attack at the Fe‐rich/α‐Al interfaces, which is then followed by localized corrosion through the eutectic areas. A more refined microstructure and the presence of Nd‐rich phases in the A356Nd alloy considerably improves its pitting corrosion resistance compared with the A356 alloy which shows severe pitting corrosion.